The dramaturgy of gambang semarang art company (GSAC) a strategy towards tourism art - Damar Tri Afrianto; Putut Bayu Santiko (ASSOCIATION FOR SCIENTIFIC COMPUTING ELECTRICAL AND ENGINEERING (ASCEE), 2021)
This research answers how the dramaturgical innovation of the Gambang Semarang Art Company (GSAC) performance is to go to tourism. The main objective is to explain GSAC's strategy in dealing with the tourism industry through dramaturgical innovation. This study uses a qualitative interpretive research method. Data were obtained through interviews and performance observations. The results showed that the Dadung Kepuntir story GSAC performance-inspired innovation and brought out new creativity. In addition, it gave rise to a form of presentation to enrich the repertoire of Gambang Semarang performances. The GSAC community is fully aware of the need for the arts for tourism. This can be seen from the approach to the show, which uses an aesthetic approach to commercialism. The aesthetics of commercialism is stated as the principles of managing the art forms of Gambang Semarang performed by the Gambang Semarang Art Company based on the attractiveness, fascination, and provocation of the attention of the mass audience of Gambang Semarang